To Some Ethical and Legal Issues of Human Embryo and Gamete Cryopreservation - Hryhorenko, Olena V.; Petrushko, Marina P. (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2):179.